Modeling Scenarios for Cultural Resilience Among Youth in Conditions of Hybrid Information Threats - Lupyna, Artem (Вісник гуманітарних наук, 2026)
This article examines the problem of modeling cultural resilience scenarios among youth under conditions of hybrid information threats as a complex social phenomenon shaped by the digital environment, mass communications, transformations of cultural identity, and shifts in the system of social values. The purpose of this study is to identify the social mechanisms underlying the formation of cultural resilience among youth and to develop a scenario-based model of its evolution amid information turbulence, increasing manipulative influences, and the proliferation of disinformation. Methods. The methodological framework of this study is grounded in systemic, sociocultural, and scenario-based approaches, complemented by methods of scholarly source analysis, generalization, social modeling, comparative analysis, and interpretation of data on the information behavior of youth in the digital environment. Results. The study identified the principal determinants of cultural resilience, including the level of critical thinking, digital literacy, social trust, engagement in cultural practices, the degree of civic identity formation, the capacity for selective information processing, and resistance to manipulative influences. A typology of youth cultural resilience scenarios was substantiated, comprising adaptive, resistant, transformational, and disorientation models that reflect distinct patterns of response to information influences and varying levels of social integration. The study demonstrated that the effectiveness of cultural resilience depends on the interaction between individual personal resources and the social environment, particularly educational institutions, the media landscape, family, informal communities, and civil society. The proposed model enables the forecasting of youth behavioral trajectories and the development of social strategies to counteract destructive information influences. Conclusions. The findings confirm the necessity of a comprehensive interdisciplinary approach to strengthening the cultural resilience of the younger generation as a vital factor in social stability, information security, and the preservation of societal cultural integrity under contemporary hybrid challenges